2016
DOI: 10.18568/1980-4865.11149-62
|View full text |Cite
|
Sign up to set email alerts
|

The role of technological capability in the internationalization of the company and new product success: a systematic literature review

Abstract: <span style="font-size: 12.0pt; line-height: 150%; font-family: 'Times New Roman',serif; mso-fareast-font-family: Calibri; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The constant changes in the existing corporate environment require organizations to submit high speed to adapt to hypercompetitive scenarios. Technological capability can promote company internationalization as it enables the formation of strategic partnerships, investment in R&amp;D, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…The development of firms depends on the degree to which their technological capabilities enable them to create new products (Guerra and Camargo, 2016). Technological capability has an important place in product innovation, as it has a positive effect both on the transformation of market knowledge into product innovation and also directly on product innovation.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…The development of firms depends on the degree to which their technological capabilities enable them to create new products (Guerra and Camargo, 2016). Technological capability has an important place in product innovation, as it has a positive effect both on the transformation of market knowledge into product innovation and also directly on product innovation.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…(Nazeer et al, 2021). In the consulting process, the age of the company and the experience of the company's managers play an important role in determining the absorption of knowledge (Guerra & Camargo, 2016), Second, implementing standard operating procedures that prioritize customer satisfaction and consistently following the latest standards through the application of the exploitation process of the knowledge gained. In research conducted bySrivastava et al, (2015), states that companies that have strong technological capability have a high ability to utilize knowledge obtained from external parties.…”
Section: Discussion Of Research Outcome the Effect Of Technological C...mentioning
confidence: 99%
“…So it can be concluded that technological capability in food and beverage packaging companies is an important resource for companies that must be managed effectively to develop products that are in line with market trends and to introduce new products from time to time. (Guerra & Camargo, 2016).…”
Section: The Effect Of Technological Capability On Firm Performancementioning
confidence: 99%
“…For instance, MMDAs are responsible for developmental interventions and projects needed for the welfare of communities and the abilities to use technological equipment in meeting this need is vital. Also included are other hard skills such as fundraising skills to be able to procure the financial and in-kind resources necessary for efficient operations (Guerra and Camargo, 2016; Salisu and Abu Bakar, 2020).…”
Section: Theoretical and Conceptual Reviewmentioning
confidence: 99%